Study on Potential Appraisal Metrics for Managerial Employees - Sivaramakrishnan, G.; Sulaiman, Mohammed (Prabandhan: Indian Journal of Management, 2015)
Performance appraisal system has a dual objective - employee development for the corporates and career development for the employees. This objective is better fulfilled by a potential appraisal system, which tells about an employee’s capability to successfully assume a new role demanded by the organization. Promotion is awarded on the basis of employees’ present performance in their existing role; responsibilities and functions that are substantially different from those of higher responsibilities. In organizations, it is a normal practice to promote people on the basis of their past performance, and this practice is hierarchical in nature. In an organization, the functions and responsibilities given to an employee depend upon the role played by Him/Her in the organizational hierarchy. The capabilities required to perform one role may not be the same as those required to perform a role with higher responsibility having different functions. The major inadequacy of the present performance appraisal system for promotions is based on performance appraisals that are dependent on past performance. Hence, to promote young talent, who need to cope with the demanding needs of a liberalized business era, a potential appraisal system to appraise the employees was thought to be a fitting approach for the present study. The desired metrics to measure the same were considered and discussed in this research paper.